Outcome measures to be considered on asthma in elderly. Issue 3 (June 2019) - González-Díaz, Sandra Nora; Villarreal-Gonzalez, Rosalaura Virginia; Lira-Quezada, Cindy Elizabeth De; Guzman-Avilan, Rosa Ivett
Abstract : Purpose of review: Asthma is a chronic heterogeneous respiratory disease which is characterized by airflow limitation and variable respiratory symptoms. Asthma in patients more than 65 years of age has an important negative impact on quality of life. The pathophysiology and treatment of asthma in older patients are not as well identified as in younger groups of ages. In this review we intend to outline characteristics found in elderly adults which distinguish them from other age groups of patients with asthma. Recent findings: With increasing age, there are alterations in the innate and adaptive immune responses, known as 'immunosenescence.' These age-associated modifications include an altered response after a pathogenic exposure or tissue injury, moderately mediated through an irreversible loss of cellular replication and defective tissue repair. Summary: Asthma is a consequence of complex gene–environment interactions, with diversity in clinical presentation and the type and intensity of airway inflammation and remodeling. Age-associated changes in lung physiology and morphology may occur and contribute to asthma. Aging is correlated with a notable decrease in elastic recoil, greater chest wall rigidity, and poor respiratory muscle strength. Underreporting of symptoms by elderly patients is common because of multiple underlying causes. Video abstract: http://links.lww.com/COAI/A17 . Abstract : Supplemental Digital Content is available in the text